Evaluación de la calidad mediante inspección visual de discontinuidades en uniones soldadas en base al código aws - Castillo Vilela, Oscar Emerson (2019)
In the present work of descriptive research, quality has been evaluated by visual inspection of discontinuities in welded joints based on the AWS code D1.1 of welded joints by manual electric arc welding process with coated electrode, with the following characteristics: 6 "x 4" x 2 "x 0.25" fillet welds and a 6 "x 4" x 0.25 "slot weld The type of discontinuities was identified and dimensioned using gauges for visual inspection recommended by the American Welding Society. and the evaluation was carried out according to the AWS D1.1 welding code. identifying surface discontinuities such as porosity, lateral undercut, lack of filling, overlaps, longitudinal and transverse cracks to the weld bead and arc strike. The results suggest that visually what apparently constitutes a defect, is only a discontinuity according to the corresponding evaluation, concluding that the type and size of the discontinuity in the specimens of the welded joints vary and its possible rejection is assessed by constituting a defect with the applicable code.